EFFORTS TO IMPROVE STUDENTS' FOREARM PASS ABILITY THROUGH TEAM GAME TOURNAMENT (TGT) LEARNING MODEL - Irmayenti Irmayenti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The background of this study was that many students were not able to do forearm pass properly. Besides, many students did not focus on carrying out learning activities. This study aimed to improve students' ability to do forearm pass at grade 7 of SMPN 9 Mandau by implementing TGT learning model in order to encourage students to perform they best. This study was conducted in September 2019. The subjects in this study were 29 students consisting of 14 boys and 15 girls. The instrument of this research was an observation sheet. The results showed that in the first cycle as many as 15 students (51.72%) reached Good criteria. However, this achievement was considered not to reach the specified accomplishment indicators so that it needed to be improved in the next cycle. In the second cycle, it increased to 93.09% which meant that 27 students were able to pass well. Based on the results of this study, it was concluded that implementing TGT improved the students’ forearm pass ability at grade 7 of SMPN 9 Mandau.